Space-Valence Priming with Subliminal and Supraliminal Words - Ansorge, Ulrich; Khalid, Shah; König, Peter (Frontiers in Psychology, 2013)
To date it is unclear whether (1) awareness-independent non-evaluative semantic processes influence affective semantics and whether (2) awareness-independent affective semantics influence non-evaluative semantic processing. In the current study, we investigated these questions with the help of subliminal (masked) primes and visible targets in a space-valence across-category congruence effect. In line with (1), we found that subliminal space prime words influenced valence classification of supraliminal target words (Experiment 1): Classifications were faster with a congruent prime (e.g., the prime ‘up’ before the target ‘happy’) than with an incongruent prime (e.g., the prime ‘up’ before the target ‘sad’). In contrast to (2), no influence of subliminal valence primes on the classification of supraliminal space targets into up- and down-words was found (Experiment 2). Control conditions showed that standard masked response-priming effects were found with both subliminal prime types, and that an across-category congruence effect was also found with supraliminal valence primes and spatial target words. The final Experiment 3 confirmed that the across-category congruence effect indeed reflected priming of target categorization of a relevant meaning category. Together, the data jointly confirmed prediction (1) that awareness-independent non-evaluative semantic priming influences valence judgments.